2008
DOI: 10.1103/physrevb.77.075107
|View full text |Cite
|
Sign up to set email alerts
|

Cellular dynamical mean-field theory of the periodic Anderson model

Abstract: We develop a cluster dynamical mean field theory of the periodic Anderson model in three dimensions, taking a cluster of two sites as a basic reference frame. The mean field theory displays the basic features of the Doniach phase diagram: a paramagnetic Fermi liquid state, an antiferromagnetic state and a transition between them.In contrast with spin density wave theories, the transition is accompanied by a large increase of the effective mass everywhere on the Fermi surface and a substantial change of the Fer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Generally speaking, the outlined "recipe for pseudogap", should be actually more general than the somewhat specific model that we explored. Indeed other studies 29,41,42 of hybridized localized and itinerant electrons have reported similar features in the spectrum. These studies together with ours seem to support a common scenario in which hybridizing localized and itinerant electrons can easily produce a metallic phase with a very low coherence temperature, as it happens in heavyfermions.…”
Section: Discussionsupporting
confidence: 67%
“…Generally speaking, the outlined "recipe for pseudogap", should be actually more general than the somewhat specific model that we explored. Indeed other studies 29,41,42 of hybridized localized and itinerant electrons have reported similar features in the spectrum. These studies together with ours seem to support a common scenario in which hybridizing localized and itinerant electrons can easily produce a metallic phase with a very low coherence temperature, as it happens in heavyfermions.…”
Section: Discussionsupporting
confidence: 67%
“…The Kondo effect as well as the heavy-fermion state are well described, and the phase diagram of the Kondo lattice model within DMFT has been investigated by a number of authors before. [13][14][15][16][17][18][19][20][21][22][23] In the original DMFT approach, one is interested in a homogeneous lattice, so that each site can be described by the same self-energy. Because in the superlattice the system is inhomogeneous, i.e., there are different kinds of layers with different physical properties, different lattice sites cannot be approximated with the same self-energy.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Cellular DMFT rewrites the lattice problem in terms of supercells 9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]88 . The lattice-site index is replaced by a double index -index of the supercell and the index of the site within the supercell.…”
Section: Cellular Dmft (Cdmft)mentioning
confidence: 99%